A STUDY ON PROBLEMS FACED BY WOMEN EMPLOYEES IN THE GARMENT INDUSTRY WITH SPECIAL REFERENCE TO COIMBATORE DISTRICT - Dr.S.Renugadevi, Ms.K. Sandhiya, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Garment manufacturing means sewing, cutting, making, processing, repairing, finishing, assembling, dyeing, altering a garment’s design, causing another person to alter a garment’s design, affixing a label to a garment, or otherwise preparing any garment or any article of wearing apparel or accessories designed or intended to be worn by any individual, including, but not limited to, clothing, hats, gloves, handbags, hosiery, ties, scarfs, and belts. The Garment Industry of Coimbatore is an Rs -one lakh industry. Almost 33 % of its knitwear production and about 20% of its woven garment production, both by volume, enters export markets. Overall, about 25 % of the volume of its garment production goes into export markets, leaving 75 % for domestic consumption.